Roman defeat, Christian response, and the literary construction of the Jew - Olster, David Michael, 1954- (Middle Ages series., 1994)
Olster explores Byzantine Christian reactions to the catastrophic Persian and Arab invasions, challenging long-held assumptions that divided "religious" from "secular" literature and exempted religion from contemporary social, political, and intellectual discourse